Outlook of Pharmacoeconomics and its status in Nepal - Paudel, Sabita (Journal of College of Medical Sciences-Nepal, 2018)
Pharmacoeconomics is a branch of health economics which is derived from latin word “Pharmacon”- and “Economia”- It deals with the economic aspect of health that is the costs of health services. There are different types of costs which is affecting the health services. There is not only the direct medical cost, but also direct nonmedical cost, indirect nonmedical costs and intangible cost. The consequences of therapy are evaluated from economic, clinical and humanistic perspective, also known as the ECHO model. There are partial and full pharmacoeconomic analyses. The partial analyses are cost of illness and cost of consequence. The full analyses are cost effective, cost benefit, cost utility and cost minimization analyses. The cost effective analysis is the most commonly used analysis.